(untitled) (Biomedical Research and Therapy, 2022)
Introduction: Ulcerative colitis (UC) and other inflammatory bowel diseases (IBDs) are common chronic, inflammatory gastrointestinal diseases. Due to their antioxidant, anti-inflammatory, and antibacterial properties, polyphenols are beneficial in the treatment of IBD. Caffeine acid phenethyl ester (CAPE) has been shown to have cytotoxic, antibacterial, antioxidant, and anti-inflammatory effects. This study focuses on the biochemical and molecular levels of the mode of action of CAPE in DSS-induced UC in rats. Methods: Thirty male Wistar rats were distributed into five groups, with six rats in each group: group I was administered 3 mL of distilled water orally, group II was administered CAPE (10 mg/kg.b.w.) orally, group III was administered 5% DSS orally, group IV was administered 5% DSS and CAPE (10 mg/kg.b.w.) orally; and group V was administered 5% DSS and sulfasalazine (100 mg/kg b.w.) orally. Results: Individually, oral treatment with CAPE or sulfasalazine significantly ameliorated body weight, DAI score, and colon length in DSS-induced colitis and raised blood PLT count, NO, NF-kß, and vitamin C levels. In addition, animals given CAPE had a considerable increase in colon GSH, GPx, CAT, and SOD levels compared with rats given DSS. Compared with the DSS control group, colon TBAR, IL-6, and INF-ɣ were lower in the CAPE-treated rats. Histopathological examination revealed that CAPE treatment caused tissue injury and improved vanin-1, AKT, and miRNA-203 genes in the distal colon and triggered apoptosis. Conclusions: The gastroprotective impact of CAPE was more noticeable than sulfasalazine. CAPE treatment caused biochemical and histopathological improvements, indicating that CAPE may have antioxidant and anti-inflammatory effects in colitis; therefore, CAPE may be a potential therapeutic agent for the amelioration of IBD. This finding is promising for future therapies and research goals.